Konsep Pahala Ilahi dalam Tasawuf Sunni: Analisis Pemikiran Imam Al-Nawawi tentang Ikhlas, Amal, dan Karunia Tuhan - Ali Yusuf Muzaki; Zakaria Zakaria; Ridwan Ridwan; Agus Salim; M. Farid Zaini (Yayasan Haiah Nusratul Islam, 2026)
The concept of divine reward in the Sunni Sufi tradition intersects with issues of sincerity (ikhlash), the nature of deeds, and divine grace. Imam al-Nawawi (631-676 AH), as a central figure in Shafi'i-Ash'ari scholarship, holds a distinctive view on the relationship between sincerity, deeds, and divine reward. Previous studies have focused on reward within Mutazilah-Ashariyyah theological discourse and in interdisciplinary hadith approaches as offered by Azhary et al. in Nabawi Journal (2024), leaving the Sufi dimension of al-Nawawi's thought underexplored. This study asks: (1) how does al-Nawawi conceptualize divine reward from a Sunni Sufi perspective; (2) how do sincerity, deeds, and divine grace interrelate in his thought. A library research method with descriptive-analytical and comparative approaches is employed. Results indicate that al-Nawawi views sincerity as the primary condition for the acceptance of deeds, while divine reward remains entirely a grace that cannot be demanded. This affirms the unity of shari'ah, Sufism, and Ash'ari theology in al-Nawawi's thought.